Usinagem de ferro fundido vermicular com ferramenta de corte à base de alumina magnésio - Sousa, Taíse Azevedo de [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The development of new materials is extremely important, due to the need to obtain materials with good properties and low cost. There is a continuing need to improve tools for machining materials that have high strength at elevated temperatures that meet the vermicular cast iron. Small advances in the development of new tools could mean important aspects in the field of machining, in addition to making the market more competitive. The set of production and application of ceramic cutting tools in the machining processes of vermicular cast iron (GJV450) needs further advances, being an object of great industrial interest. In this context, the present work determined the best application condition of the ceramic tools based on Alumina (Al2O3), doped with magnesium oxide (MgO) on a laboratory scale, in the machining without cutting fluid of the vermicular iron class GJV450 in comparison with a commercial carbide tool coated with alumina, based on the need for machining vermicular cast iron in industries and foundries. For turning vermicular cast iron with a ceramic tool, the parameters used were cutting speeds of 300-350-400-450-500-550-600-650 m / min; feed of 0.1-0.3 mm / rev and machining depth of 0.5 -1.0 mm and for the carbide tool, cutting speeds of 150-250-350-450 m / min; feed rate of 0.1-0.3 mm / rev and machining depth of 0.5 -1.0 mm. The previously defined input variables (Vc, f, ap), were correlated with the output variables such as roughness (Ra and Rt), power, acoustic emission, flank wear (Vb) and vibration. Taguchi design of experiments was used with the definition of smaller is better, one can evaluate the effects of the input factors that affected the response variables. It was found that the advance (f) is an influential factor with a tendency for growth except for the acoustic emission, power, and vibration for carbide. For ceramics, the feed (f) was influential except for the power and flank wear. The ceramic alumina tool presented better machining conditions in terms of flank wear, with a cutting speed Vc = 350 m / min, while the carbide showed a better condition with cutting speed Vc = 150 m / min. The wear mechanisms were analyzed and for ceramics, the wear was predominantly abrasive and, in the carbide, the diffusive mechanism occurred, the machining conditions were favorable to the use of the ceramic tool.

O desenvolvimento de novos materiais apresenta extrema importância, devido a necessidade de obtenção de materiais com boas propriedades e baixo custo. Existe uma contínua necessidade de melhoria das ferramentas para usinagem de materiais que apresentam alta resistência em temperaturas elevadas as quais atendam ao ferro fundido vermicular. Pequenos avanços no desenvolvimento de novas ferramentas poderão significar importantes aspectos no campo da usinagem, além de tornar o mercado mais competitivo. O conjunto produção e aplicação de ferramentas de corte cerâmica nos processos de usinagem do ferro fundido vermicular (GJV450) necessita de maiores avanços, sendo objeto de grande interesse industrial. Neste contexto, o presente trabalho determinou a melhor condição de aplicação das ferramentas cerâmicas à base de Alumina (Al2O3), dopada com óxido de magnésio (MgO) em escala laboratorial, na usinagem sem fluido de corte do ferro vermicular classe GJV450 em comparativo com uma ferramenta comercial de metal duro revestida de alumina, fundamentado na necessidade de usinagem do ferro fundido vermicular nas indústrias e fundições. Para o torneamento do ferro fundido vermicular com ferramenta cerâmica os parâmetros utilizados foram velocidade de corte de 300-350-400-450-500-550-600-650 m/min; avanço de 0,1-0,3 mm/rev e profundidade de usinagem de 0,5 -1,0 mm e para a ferramenta de metal duro, velocidade de corte de 150-250-350-450 m/min; avanço de 0,1-0,3 mm/rev e profundidade de usinagem de 0,5 -1,0 mm. As variáveis de entrada previamente definidas (Vc, f, ap), foram correlacionadas com as variáveis de saída como rugosidade (Ra e Rt), potência, emissão acústica, desgaste de flanco (Vb) e vibração. Utilizou-se o planejamento de experimentos Taguchi com a definição de menor é melhor, pode-se avaliar os efeitos dos fatores de entrada que afetaram as variáveis resposta. Verificou-se que o avanço (f) é um fator influente com tendência de crescimento com exceção da emissão acústica, potência e vibração para metal duro. Para cerâmica o avanço (f) foi influente com exceção da potência e desgaste de flanco. A ferramenta cerâmica de alumina apresentou melhores condições de usinagem quanto ao desgaste de flanco, com uma velocidade de corte Vc = 350 m/min, enquanto o metal duro apresentou melhor condição com velocidade de corte Vc = 150 m/min. Os mecanismos de desgaste foram analisados e para a cerâmica o desgaste foram predominantemente abrasivo e no metal duro ocorreu o mecanismo difusivo, as condições de usinagem se apresentaram favoráveis a utilização da ferramenta cerâmica.
Machining of vermicular cast iron with cutting tool based on magnesium alumina
Keywords: Usinagem; Ferro fundido; Material Cerâmico; Ceramic tools; Hard metal; Dry machining; Vermicular Cast Iron